Numerical simulation of turbulent flow in high-head impeller of centrifugal compressor - A. M. Danilishin; Yu. V. Kozhukhov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents the results of viscous flow modeling using different turbulence models in the Ansys CFX program for the D. Eckardt and H. Krain stage. The impellers are with an outlet angle of 90 and 60 degrees. Isentropic efficiency and the total pressure ratio are compared with the experimental data. The evaluation of the static pressure contours structure at the impeller shroud is made. Recommendations for qualitative modeling of high-head stages are given.